Risk Assessment and Regulatory Exploration of the Lubrication Coating on Intravascular Medical Devices - Xu, Yun; Ming, Zhang-Yin (Frontiers in Cardiovascular Medicine, 2022)
Lubricious polymer coatings are increasingly used on intravascular devices to facilitate application processes. Although increasing reports about the separation and downstream embolism of polymer particles, this iatrogenic polymer embolism has not been paid enough clinical attention for many years. This article reviews the hazard of coating separation and the difficulty to find it. Furthermore, it proposes the scientific evaluation concept and regulatory exploration to solve the problems.